Memória, escrita e exílio em Bartolomeu Campos de Queirós - Christian Victor de Oliveira Coelho (2022)
This article presents an interpretation of the work of the writer Bartolomeu Campos de Queirós, taking memory and exile as central aspects in the construction of his literary text. For this, we will analyze how the author intertwines the memories of childhood with his fantasy, articulating autobiographical and fictional elements. Then we will approach the theme of exile, in its concrete dimension and in its symbolic effects, in a movement that goes from negative experience to aesthetic resignification. In addition, we emphasize the presence of metalinguistic reflections and the relations of the fictional text with the historical contex .